2020
DOI: 10.3389/fmicb.2020.601555
|View full text |Cite
|
Sign up to set email alerts
|

A Novel, Broad-Acting Peptide Inhibitor of Double-Stranded DNA Virus Gene Expression and Replication

Abstract: Viral infections are a global disease burden with only a limited number of antiviral agents available. Due to newly emerging viral pathogens and increasing occurrence of drug resistance, there is a continuous need for additional therapeutic options, preferably with extended target range. In the present study, we describe a novel antiviral peptide with broad activity against several double-stranded DNA viruses. The 22-mer peptide TAT-I24 potently neutralized viruses such as herpes simplex viruses, adenovirus ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 59 publications
3
26
0
Order By: Relevance
“…In this study we have used TAT peptide as a control and we did not observe any antiviral activity associated with using three different strains of HSV-1, three different cell lines and two different strains of mice. Similar to this study, TAT alone did not have any antiviral activity against two different strains of HSV-1, adenovirus type 5, cytomegalovirus, vaccinia virus, and simian virus 40 in cell culture models [46]. In addition, no antiviral activities associated with the TAT control peptide was reported for influenza virus [47,48], Ebola virus [49], Epstein-Barr virus [50], or Japanese encephalitis virus [51].…”
Section: Plos Pathogenssupporting
confidence: 79%
“…In this study we have used TAT peptide as a control and we did not observe any antiviral activity associated with using three different strains of HSV-1, three different cell lines and two different strains of mice. Similar to this study, TAT alone did not have any antiviral activity against two different strains of HSV-1, adenovirus type 5, cytomegalovirus, vaccinia virus, and simian virus 40 in cell culture models [46]. In addition, no antiviral activities associated with the TAT control peptide was reported for influenza virus [47,48], Ebola virus [49], Epstein-Barr virus [50], or Japanese encephalitis virus [51].…”
Section: Plos Pathogenssupporting
confidence: 79%
“…The linear, 9-mer peptide I24 comprising the sequence CLAFYACFC (Figure 1) was identified as an inhibitor of "foreign" gene expression due to its ability to selectively block transcription from a transfected eukaryotic plasmid-DNA when added together with the DNA to the transfection reaction [23].…”
Section: The 9-mer Peptide I24 Blocks Rna Synthesis and Initiation Co...mentioning
confidence: 99%
“…Earlier data have shown that coupling of I24 to a cationic peptide, such as the TAT peptide (residues 48-60) from the HIV-1 transactivator protein (Figure 1), can strongly enhance the inhibitory effect of I24 on gene expression from a eukaryotic expression plasmid transfected with the peptide into cells. Moreover, coupling of I24 to TAT (TAT-I24; Figure 1) not only affected transfected DNA but also exerted a broad-spectrum antiviral activity against several double-stranded DNA viruses, including herpes simplex viruses, cytomegalovirus, vaccinia virus, adenovirus type 5 and SV 40 polyomavirus, an effect which was not seen with I24 alone [23]. It was, therefore, speculated that the TAT peptide contributes to the antiviral effects of the fusion peptide.…”
Section: The Fusion Of Peptide I24 To the Tat Peptide Binds Double-st...mentioning
confidence: 99%
See 2 more Smart Citations